Mycotoxin mixtures in food and feed: holistic, innovative, flexible risk assessment modelling approach: MYCHIF. Issue 1 (24th January 2020) - Battilani, Paola; Palumbo, Roberta; Giorni, Paola; Dall'Asta, Chiara; Dellafiora, Luca; Gkrillas, Athanasios; Toscano, Piero; Crisci, Alfonso; Brera, Carlo; De Santis, Barbara; Rosanna Cammarano, Rosaria; Della Seta, Maurella; et al.
Abstract : Mycotoxins are toxic compounds mainly produced by fungi of the genera Aspergillus, Penicillium and Fusarium . They are present, often as mixtures, in many feed and food commodities including cereals, fruits and vegetables. Their ubiquitous presence represents a major challenge to the health and well being of humans and animals. Hundreds of compounds are listed as possible mycotoxins occurring in raw and processed materials destined forhuman food and animal feed. In this study, mycotoxins of major toxicological relevance to humans and target animal species were investigated ina range of crops of interest (and their derived products). Extensive Literature Searches (ELSs) were undertaken for data collection on: (i) ecology and interaction with host plants of mycotoxin producing fungi, mycotoxin production, recent developments in mitigation actions of mycotoxins in crop chains (maize, small grains, rice, sorghum, grapes, spices and nuts), (ii) analytical methods for native, modified and co‐occurring mycotoxins (iii) toxicity, toxicokinetics, toxicodynamics and biomarkersrelevant to humans and animals (poultry, suidae (pig, wild boar), bovidae (sheep, goat, cow, buffalo), rodents (rats, mice) and others (horses, dogs), (iv) modelling approaches and key reference valuesfor exposure, hazard and risk modelling. Comprehensive databases were createdusing EFSA templatesand werestored in the MYCHIF platform.A range of approaches were implemented to explore the modelling of external andinternal exposure as well as dose‐response of mycotoxins in chicken and pigs. In vitro toxicokinetic and in vivo toxicity databases were exploited, both for single compounds and mixtures. However, large data gaps were identifiedparticularly with regards toabsence of common statistical and studydesigns within the literature and constitute an obstacle for the harmonisation of internal exposure and dose‐response modelling. Finally, risk characterisation was also performed for humans as well as for two animal species (i.e. pigs and chicken) using available tools for the modelling of internal dose and a component‐based approach for selected mycotoxins mixtures.